2020
DOI: 10.3390/biom10040638
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mechanisms of Eosinophil Accumulation in Eosinophilic Pneumonia

Abstract: Eosinophilic pneumonia (EP), including acute EP and chronic EP, is characterized by the massive pulmonary infiltration of eosinophils into the lung. However, the mechanisms underlying the selective accumulation of eosinophils in EP have not yet been fully elucidated. We reported that bronchoalveolar lavage fluid (BALF) from EP patients induced the transmigration of eosinophils across endothelial cells in vitro. The concentrations of eotaxin-2 (CCL24) and monocyte chemotactic protein (MCP)-4 (CCL13), which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…MIP-1β is a well-known chemokine produced by various cells, such as neutrophils, epithelial cells, B cells, T cells, and eosinophils [ 55 ]. In a previous study, MIP-1β was found to have chemo-attractant activity for eosinophils [ 56 ]. These chemo-attractant activities of MIP-1β can cause the infiltration of eosinophils into the lungs and bronchi, which results in allergic lung inflammation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…MIP-1β is a well-known chemokine produced by various cells, such as neutrophils, epithelial cells, B cells, T cells, and eosinophils [ 55 ]. In a previous study, MIP-1β was found to have chemo-attractant activity for eosinophils [ 56 ]. These chemo-attractant activities of MIP-1β can cause the infiltration of eosinophils into the lungs and bronchi, which results in allergic lung inflammation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-5 acts synergistically with eotaxins, a variety of C-C motif chemokine ligands (CCLs), which are selective chemotactic factors that mediate the migration and recruitment of these cells into the body tissues and their activation [30]. Eotaxin (CCL11), eotaxin-2 (CCL24), and eotaxin-3 (CCL26), among others, bind to CCchemokine receptors-3 (CCR3) on eosinophil cell membranes and can induce chemotaxis in allergic inflammation [31] (Figure 1). 5-oxo 6, 8, 11, 14-eicosatetraenoic acid (5-oxo-ETE) is another eosinophil chemoattractant [32].…”
Section: Figurementioning
confidence: 99%
“…For circulating eosinophils to accumulate in asthmatic airways, they must adhere to and then migrate across vascular endothelial cells. These processes are largely regulated by cytokines/chemokines produced by various cells, including Th2 cells [44][45][46]. Increased adhesion of peripheral blood eosinophils and increased chemotactic activity of eosinophils into the airways are observed during the allergen exposure period in birch pollen asthma, and allergen immunotherapy suppresses increased eosinophil adhesion and chemotactic activity [3,32].…”
Section: Mechanisms Of Allergen Immunotherapymentioning
confidence: 99%